Model-prototype based flight test: Bringing flight control engineering to life for a reusable rocket with flightgear - Aditya Tri Oktaviana; Mochammad Ibnu Alwan; Adhi Kusumadjati; Mikael Syväjärvi (FoundAE, 2026)
ackground: Reusable rocket technology has gained significant attention due to its potential to reduce launch costs, development time, and environmental impact. However, conventional development and flight testing of reusable rockets require substantial financial resources and carry high risks of material loss, particularly during early-stage experimentation and in resource-constrained research or defense education environments. Aims: This study proposes a low-cost and accessible approach for reusable rocket development through a Model–Prototype Based Flight Test (MPBFT) method. The aim is to integrate mathematical flight control modeling, prototype-level implementation, and real-time three-dimensional visualization into a single co-simulation framework that enables virtual flight testing without physical launch, specifically for reusable rocket descent and landing maneuvers. Method: The MPBFT framework integrates a dynamic model of the reusable rocket developed in MATLAB/Simulink based on rigid-body flight dynamics, with explicit mathematical formulations including governing differential equations, state-space representation, and closed-loop transfer function. A derivative-based proportional–integral–derivative (PID) controller was designed to regulate the rocket's pitch attitude. Real-time 3D visualization was achieved through co-simulation with FlightGear via UDP communication at 50 Hz. Controller gains were tuned iteratively (Kp=12.5, Ki=0.08, Kd=5.2), and robustness was assessed under parameter perturbations (+20% moment of inertia, +15% damping, step disturbance). Results: Simulation results demonstrated stable closed-loop attitude control with the following quantitative metrics: 8.2% maximum overshoot, 3.87 s settling time (±2%), 0.014° steady-state error, damping ratio of 0.62, integral absolute error of 8.42°·s, and control effort (RMS) of 3.21 N·m. Robustness analysis confirmed that all perturbed configurations remained stable and within acceptable thresholds (overshoot <15%, settling time <6 s, steady-state error <0.1°). The co-simulation successfully provided synchronized real-time 3D visualization of rocket pitch motion during descent. Conclusion: The MPBFT framework is an effective and economical alternative for reusable rocket flight control testing, particularly suitable for research, defense aerospace education, and resource-constrained environments. Future work will extend the framework to multi-axis 6-degree-of-freedom dynamics, hardware-in-the-loop simulation, actuator and sensor modeling, and physical subscale flight validation to further enhance fidelity and applicability for advanced reusable rocket control system development.